anonymous
  • anonymous
Which shows 54^2 − 46^2 being evaluated using the difference of squares method? 54^2 − 46^2 = (2916 + 2116)(2916 − 2116) = 4,025,600 54^2 − 46^2 = (54 + 46)(54 − 46) = (100)(8) = 800 54^2 − 46^2 = 2916 − 2116 = 800 54^2 − 46^2 = (54 − 46)^2 = 8^2 = 64
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@welshfella
welshfella
  • welshfella
using letters difference of 2 squares is a^2 - b^2 = (a + b)(a - b) same 2 letters in each bracket but + in one bracket and - in the other
welshfella
  • welshfella
so if you put a = 54 and b = 46 in the above you can see which choice is correct

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

welshfella
  • welshfella
54^2 - 46^2 = ( 54 + )( 54 - ) = ? can you fill in the blanks?
anonymous
  • anonymous
46?
welshfella
  • welshfella
right now you should know the correct choice
anonymous
  • anonymous
Yep :]
anonymous
  • anonymous
B correct?
welshfella
  • welshfella
yes

Looking for something else?

Not the answer you are looking for? Search for more explanations.